Adaptasi Semantik Istilah Asing dalam Terminologi Reksa Dana Bahasa Indonesia: Kajian Linguistik Terapan - Nuraini, Rani Rianti; Dwi Putri Ramadhani; Nabyla Patma Agustina; Anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study analyzes the semantic adaptation of foreign terms in Indonesian mutual fund terminology. A descriptive qualitative approach was employed to examine data sourced from documents issued by the Financial Services Authority (OJK), mutual fund prospectuses, and investment manager websites. Drawing on the theoretical frameworks of Haugen (1972) and Weinreich (1953), the study identifies four patterns of adaptation: (1) direct translation (e.g., alokasi aset [asset allocation]), (2) indirect translation (e.g., manajer investasi [investment manager]), (3) direct use of foreign terms (e.g., NAV, portfolio), and (4) semantic modification (e.g., penarikan unit [unit withdrawal] for redemption). The findings indicate that semantic adaptation plays a significant role in enriching vocabulary, reducing ambiguity, establishing terminological consistency, and supporting financial literacy. The study concludes that this process serves as a crucial strategy for bridging global concepts with local understanding, facilitating effective communication, and reinforcing the identity of the Indonesian language in the financial domain